Challenges experienced by newly employed nurse educators during transition from being expert clinicians to novice nurse educators - Tumelo Dintwe; Gopolang Gause; Leepile Alfred Sehularo (BMC Nursing)
Abstract Background Transitioning from clinical practice to academia can be unsettling, due to uncertainty around expectations. For some newly appointed nurse educators this implies relinquishing management or supervisory roles at the clinical site to being novice nurse educators. Although there are suggestions to provide clinical nurses with formal preparation to support and promote a smooth transition to academia, there is no clear plan in place to facilitate this, which leaves a knowledge gap regarding transition from a clinical role to academia. Methods An exploratory descriptive qualitative research design was used to achieve the aim of the study. Data were collected by an independent research assistant during August and September 2024 through online semi-structured individual interviews conducted on the Microsoft Teams meeting application. Criteria for ensuring trustworthiness in qualitative research as set out by Lincoln and Guba were employed. Data analysis was guided by Creswell and Creswell’s steps. Findings A total of 12 newly employed nurse educators with an experience of between 6 months to 5 years participated in the study. Two main themes emerged: newly appointed nurse educators’ workplace-related challenges during transition; and newly appointed nurse educators’ personal challenges related to transition. Theme one had seven sub-themes, while theme two had four sub-themes. Findings were further discussed in relation to the available literature. Conclusions Newly employed nurse educators’ transition from clinical practice to academia is often overlooked yet is challenging. The assumption is that newly employed nurse educators are expert clinicians, and therefore are specialists even in the academic space. However, this is not the case, because the academic environment is totally different from the clinical environment and can be overwhelming for novice nurse educators. It is recommended that more research should be conducted on support measures for newly employed nurse educators.